Membangun Generasi Sehat: Pendidikan Terintegrasi yang Menggabungkan Nilai Firman dan Pengetahuan Tentang Makanan - Norlan Goni; Edwin Melky Lumingkewas; Juwinner Dedy Kasingku (Departement of Mathematics Education, 2023)
This research is qualitative, with the aim of being able to build a healthy young generation by looking at the word and science about healthy food. From the beginning of creation until now, God has created a variety of healthy foods for us to enjoy together. With the view of science, we can more easily judge what food is proper and nutritious for our bodies. God provided his people with nutritious food in the Old Testament from the beginning of creation until the flood. By following the views of science, we are also more convinced of which foods we should eat properly. With these foods, we can have a healthy and strong body. The Bible's opinion about healthy food also agrees with the scientific view about the foods that are good for our bodies. Our body is a holy temple of God. For that reason, it is important to protect our bodies from foods that damage them. To be able to get a healthy body, we must regulate eating patterns that are not excessive so that these foods can nourish our bodies and not damage them.